2014
DOI: 10.1103/physrevb.89.140401
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous metallic ground state inBaV13O18

Abstract: We studied single crystals of BaV 13 O 18 , in which V ions with an average valence of +2.62 (3d 2.38 ) form a quasi-fcc lattice. We found that the ground state of the stoichiometric crystal is insulating, whereas that of the off-stoichiometric crystal is metallic with a large effective mass. This metallic state can be explained by the Kondo coupling between the magnetic moment existing at the lone V ion and itinerant carriers in the V tetramers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Figures 1 (b) and (c) show the reflectivity spectrum R(ω) and the optical conductivity spectrum σ(ω) derived from the Kramers-Kronig transformation of R(ω), respectively, at each phase in the equilibrium state. As discussed previously, 17 there is a peak below 0.5 eV and a broad structure between 1.5 and 3 eV in the σ(ω) spectrum in this compound, which can be assigned to the in-gap excitation (the excitation of the d electrons between V 2+ and V 3+ ) and the Mott excitation (between V 3+ and V 3+ ), respectively. Characteristic changes in the σ(ω) spectrum with the phase transitions are observed particularly in the in-gap excitation; the peak athω ∼ 0.2 eV in the HT phase (250 K) shifts to a higher frequency of ∼ 0.3 eV together with an increase in the peak height in the IT phase (160 K), whereas the peak height is decreased and the peak width is increased in the LT phase (30 K).…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Figures 1 (b) and (c) show the reflectivity spectrum R(ω) and the optical conductivity spectrum σ(ω) derived from the Kramers-Kronig transformation of R(ω), respectively, at each phase in the equilibrium state. As discussed previously, 17 there is a peak below 0.5 eV and a broad structure between 1.5 and 3 eV in the σ(ω) spectrum in this compound, which can be assigned to the in-gap excitation (the excitation of the d electrons between V 2+ and V 3+ ) and the Mott excitation (between V 3+ and V 3+ ), respectively. Characteristic changes in the σ(ω) spectrum with the phase transitions are observed particularly in the in-gap excitation; the peak athω ∼ 0.2 eV in the HT phase (250 K) shifts to a higher frequency of ∼ 0.3 eV together with an increase in the peak height in the IT phase (160 K), whereas the peak height is decreased and the peak width is increased in the LT phase (30 K).…”
supporting
confidence: 67%
“…AV 13 O 18 (A=Ba, Sr) is a series of compounds that exhibit two different types of ordered states, both of which are dominated by the d electrons on the V ions. [15][16][17] This series of compounds takes a hexagonal structure and the V ions form a quasi-fcc lattice. The HT phase of these compounds is characterized by V tetramers, in which four V ions in a rhombus shape approach each other and form a cluster, as shown in Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Details were described elsewhere. 12 Electrical resistivity was measured using a conventional four-probe method. Magnetic susceptibility was measured using a SQUID magnetometer.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it has been found that BaV 10 O 15 (in which the average valence of V is +2.8) 5-8 , Ba 2 V 13 O 22 (+3.08) 9 , and Ba 1−x Sr x V 13 O 18 (+2.63) [10][11][12] with V ions on a quasi-triangular lattice exhibit ordered states similar to that of LiVO 2 . For example, the trimerization of V ions occurs in BaV 10 O 15 at 123 K, causing the opening of a charge gap of ∼0.3 eV and a sharp increase in resistivity by three orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%